2018
DOI: 10.1111/jfpe.12878
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of sesame oil extracted from the seeds with different origins: Kinetic and thermodynamic studies under accelerated conditions

Abstract: A comparative study was carried out to identify the oxidative stability of sesame oils originated from three countries: Sudan, Turkey, and Yemen. Sesame oils were oxidized under Rancimat test conditions. Reaction rate constant (k), activation energy (Ea), activation enthalpy (ΔH ++), activation entropy (ΔS ++), and Gibbs free energy of activation (ΔG ++) were calculated according to both Arrhenius model and Eyring equation of activated complex approach. Quality parameters of the sesame oils were evaluated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
6
9
0
Order By: Relevance
“…The Gibbs free energy was positive and thus it predicted a non‐spontaneous and endergonic nature of the oxidation reaction. [ 30 ] Such findings are consistent with the reported by Elhussein et al., [ 59 ] where positive Gibbs free energy changes were monitored in sesame oil oxidation at 110–140 °C. In addition, positive enthalpy of activation ΔH ‡ > 0 and negative activation entropy ΔS ‡ < 0 were established for all samples studied.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The Gibbs free energy was positive and thus it predicted a non‐spontaneous and endergonic nature of the oxidation reaction. [ 30 ] Such findings are consistent with the reported by Elhussein et al., [ 59 ] where positive Gibbs free energy changes were monitored in sesame oil oxidation at 110–140 °C. In addition, positive enthalpy of activation ΔH ‡ > 0 and negative activation entropy ΔS ‡ < 0 were established for all samples studied.…”
Section: Resultssupporting
confidence: 91%
“…Based on the results, the oxidation reaction can be defined as endergonic and non-spontaneous which is in agreement with that reported for sesame oil. [59] Exothermic reactions led to the release of energy as heat, which led to an increase in temperature. In this regard, Hrušovský et al [61] reported that the level of propensity of vegetable oils to self-heating strongly depends on the amount of unsaturated acids in vegetable oils.…”
Section: Kinetics and Thermodynamics Parametersmentioning
confidence: 99%
“…The oxidative stability (OS) of the oils, a measure of the volatile organic acids produced during the formation of the hydroperoxides or as a result of the oxidation of carbonyl compounds and other secondary (e.g., alcohols) or tertiary oxidation products may be used for monitoring the lipid oxidation progress (Farhoosh and Hoseini‐Yazdi, ). The OS of olive and other vegetable oils (e.g., linseed, rapeseed, camelina, black cumin, evening primrose, hempseed, milk thistle, poppy, pumpkin, sunflower, cottonseed, hazelnut, sesame, among other oils) has been determined mainly using Rancimat test (Aktar and Adal, ; Ciemniewska‐Żytkiewicz et al, ; Elhussein et al, ; Farhoosh et al, ; Gharby et al, ; Gülmez and Şahin, ; Hasenhuettl and Wan, ; Kowalski et al, ; Kurtulbaş et al, ; Mateos et al, ; Morsy et al, ; Mousavi and Niazmand, ; Ostrowska‐Ligeza et al, ; Ratusz et al, ; Symoniuk et al, , , ; Yang et al, ). Other techniques have also been reported, namely, the differential scanning calorimetry (Ciemniewska‐Żytkiewicz et al, ; Kowalski et al, ; Malvis et al, ; Ostrowska‐Ligeza et al, ; Ratusz et al, ; Symoniuk et al, , , ) or the time‐domain reflectometry (Sonkamble et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…From the graph in Figure 2, we notice that the variation of genotypes affected significantly the antioxidant activity of sesame extracted oil. Elhussein et al (2018) concluded that lipid oxidation of sesame oil is greatly affected by the presence of phytonutrients, as well as its origin. When these appropriate correlations hold, we could conclude that phenolic compounds in sesame oil are predominantly responsible for its antioxidant activity.…”
Section: Antioxidant Activity By Dpph and Abts Methodsmentioning
confidence: 99%